2003
DOI: 10.1177/1356336x03009001178
|View full text |Cite
|
Sign up to set email alerts
|

Parentsí Conceptions of the Influences of Participation in a Sports Programme on Their Children and Adolescents with Physical Disabilities

Abstract: Parents of children and adolescents with physical disabilities have an important role in strengthening and supporting their children in everyday life. Children and adolescents with physical disabilities do not ordinarily have natural access to club activities, nor do they receive the same support for physical activities as their peers without disabilities. The aim of this Swedish study was to describe parents' conceptions of the influences of participation in a sports programme on their children and adolescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
8
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 8 publications
3
8
0
Order By: Relevance
“…Nevertheless, it is also of note that, even weak, playing sports on a regular basis positively predicted social and emotional functioning despite the severity of the disability. These positive links are in support of the extant literature that underlines the importance of physical activities for positive identity development of youth with disabilities 4,31–33 . Previous findings for adolescents without any disability also suggest that physical activity is helpful for positive self‐perception and confidence 30,47,48 .…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Nevertheless, it is also of note that, even weak, playing sports on a regular basis positively predicted social and emotional functioning despite the severity of the disability. These positive links are in support of the extant literature that underlines the importance of physical activities for positive identity development of youth with disabilities 4,31–33 . Previous findings for adolescents without any disability also suggest that physical activity is helpful for positive self‐perception and confidence 30,47,48 .…”
Section: Discussionsupporting
confidence: 84%
“…Similar findings were found in a study by Taub and Greer, which noted the “normalizing” role of physical activity for school‐age children with physical disabilities; physical activity contributed to the children's perceptions of physical competence, self‐worth and social integration 4 . Similarly, parents' conceptions of the positive role of sports in social integration are in line with self reports of children with physical disabilities 33 …”
supporting
confidence: 57%
See 2 more Smart Citations
“…It is important, therefore, that any support or consultation should be directed at the family to strengthen the families' resilience. This is consistent with findings from KristÈn, et al (2003), who suggested parents have a significant role in supporting the adolescent with a physical disability. Furthermore, the family dynamics may impede participation for the girls if they have other siblings also requiring care and, additionally, if the girls are a low priority in the family.…”
Section: Parentssupporting
confidence: 82%